UAV - Multispectral Point Cloud (PC) from Nybygget - Asa Research Station (Swedish University of Agricultural Sciences, 2021)
Asa Research Station (2021). UAV - Multispectral Point Cloud (PC) from Nybygget, 2018-05-04 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/-0K14W4g5eUXRdKi0ITJnkW0
Keywords: SITES Spectral; Calibration/Validation; Digital Elevation / Digital Surface Models; Ecosystem functions; Plant Phenology; Reflectance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap